The relationship between medical marijuana use and prescription pain reliever use among U.S. adults: A retrospective analysis utilizing the 2015-2019 National Survey on Drug Use and Health (NSDUH) - Tyler J. Dunn; Erin Holmes; Yi Yang; John P. Bentley; Saim Kashmiri; Sujith Ramachandran (Elsevier, 2023)
Background: Despite a number of states in the U.S. enacting medical marijuana policies, there is currently a lack of research outlining the role that individual-level factors play in predicting medical marijuana use, especially regarding use and misuse of prescription pain relievers. The overall aim of this study was to assess the prevalence of medical marijuana use in the U.S. and to identify clinical, social, and demographic predictors. Methods: A retrospective secondary database analysis was conducted utilizing five years of the National Survey on Drug Use and Health (NSUDH). A multivariable logistic regression model assessed the association between prescription pain reliever use and medical marijuana in the adult U.S. population while adjusting for substance use factors, psychiatric factors, and demographic characteristics. Results: Within the U.S. adult population from 2015 to 2019, medical marijuana use increased from 1.6% to 2.4%, while appropriate prescription pain reliever use decreased from 33.4% to 27.5%, and prescription pain reliever misuse decreased from 4.7% to 3.7%. Of all marijuana users, 15.1% resided within non-medical marijuana states. Medical marijuana users are more likely to have a serious mental illness (14.0% vs. 4.4%) and a non-marijuana related substance dependence (5.3% vs. 1.2%). Past-year medical marijuana use was significantly more likely to be reported among appropriate users of prescription pain relievers (OR = 1.99, p < .001) and misusers (OR = 1.94, p < .001) (relative to nonusers). Conclusions: Prescription pain reliever appropriate use and misuse were associated with higher odds of medical marijuana use. This study identified a potential treatment gap among individuals residing in states with no medical marijuana availability. These study findings highlight the potential benefits of medical marijuana legalization that future research can build on to guide policy making decisions.